SP5.1.8 Long term outcomes of laparoscopic magnetic sphincter augmentation for gastro-oesophageal reflux disease: High patient satisfaction with low dysphagia rates. (28th October 2021) - Tabbakh, Yasmin; Walsh, Caoimhe; Tan, Tai Joum; Nehra, Dhiren
Abstract: Aims: Laparoscopic magnetic sphincter augmentation (MSA) or LINX ® procedure is gaining popularity as a treatment for gastro-oesophageal reflux disease. We looked at the long-term outcomes of this procedure with regards to its efficacy, in particular studying the dysphagia rate in relation to the LINX ® device size. Methods: Postal questionnaires were sent to all patients who underwent MSA procedure between 2012-2019 at a single institution. Patients were asked to quantify, as a percentage, their symptom resolution, proton pump inhibitor (PPI) intake and side effects. Results: 124 patients (male:female ratio was 45:55) underwent MSA procedure, with 82 responding to the questionnaire. Patients' age range was 18-71 years (median 49). Over 90% of patients reported improvements in reflux symptoms with 75% reporting complete resolution. 67% of patients no longer required PPI medication, whilst 21% of patients had >50% reduction in their medication. Post-operative dysphagia occurred in 59% of patients at 3 months, which decreased to 16% at 1 year. There was no significant difference in size of LINX ® device used between patients with dysphagia at ≥ 1 year versus those without dysphagia at ≥ 1 year (p = 0.554). In total 3 patients (2%) required explantation of the LINX ® device. Overall 86% of patients rated their outcomes as satisfactory or very satisfactory. Conclusions: Our 7 years of experience with laparoscopic MSA has demonstrated that this procedure is safe with high patient satisfaction rates. Dysphagia, although common in the early post-operative period, usually resolves within 3-6 months and is unrelated to LINX ® device size.